Habitat study of Styphelia abnormis (Sond.) J.J.Smith. in Manitalu Hill, East Waigeo Nature Reserve, Waigeo Island, West Papua - DEDEN MUDIANA (Society for Indonesian Biodiversity, 2008)
Styphelia abnormis (Sond.) J.J. Smith is a member of family Epacridaceae that grows in East Waigeo Nature Reserve (Cagar Alam Waigeo Timur). An inventory was done using 30 sampling plots of 2 x 2 m2. The results were: density 2.375 per m2 and presence 90%. This species grew as a shrub on ultramafic soil in open hilly areas at 50-80 above sea level (a sl). Styphelia abnormis is a plant species that can grow on ultramafic soil in East Waigeo NR.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Styphelia abnormis, habitat, East Waigeo Nature Reserve (Cagar Alam Waigeo Timur).